Wide hybridization between wild and cultivated species of Helianthus annuus and morphological characterization of interspecific hybrids: WIDE HYBRIDIZATION BETWEEN WILD AND CULTIVATED SPECIES OF HELIANTHUS ANNUUS - VIKAS KULKARNI; ASWINI CHUKKA; M Y KENGANAL (Journal of Oilseeds Research, 2020)
The present study was undertaken to understand cross-compatibility between two genotypes of cultivated Helianthus annuus L. and three accessions of wild annual diploid H. annuus accessions, ANN-61, ANN-98 and ANN-114. The derived six interspecific hybrids were evaluated for morphological characters and Alternaria blight incidence under field conditions. The six interspecific crosses were recorded with anthocyanin pigmentation on petiole, stem and stigma and leafserration resembling wild parents whereas some of the characters like cordate leaf shape resembled cultivated parents. Stem pubescence was intermediary between wild and cultivated parents confirming the hybrid nature of crosses. The interspecific crosses recorded medium resistant reaction to Alternaria leafspot which has been transferred fromresistant wild accessions into susceptible cultivated genotypes. Themeiotic abnormalities were not observed in interspecific crosses resulting in higher pollen fertility of 95%. The present study represents successful crossing between cultivated and diploid wild species and possibility of developing Alternaria resistant inbred lines with high self fertility in sunflower.